MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI BERMAIN DENGAN MEDIA HULAHOOP PADA ANAK KELOMPOK B PAUD AL-SYAFAQOH KABUPATEN REJANG LEBONG - Reni Novitasari; M Nasirun; Delrefi D. (Universitas Bengkulu, 2019)
The problem in this research is whether through the activity of playing with media hula hoop can improve motor abusive ability of child. The purpose of this Classroom Action Research is to develop gross motor skills in the jumping of children on the strength and balance effects on the group B children in PAUD Al-Syafaqoh Rejang Lebong District. This study proved that playing with hula hoop media can improve the development of gross motor abilities of children. Evidenced by the increase of Rough Motor Capacity in children, seen in the first cycle meeting I on the aspect of strength and balance aspects of the average value reached 2.27 with the criteria Enough, then in cycle II The third meeting reached 4.3 with the criteria Good.